Hot corrosion behaviour of Nickel-200 alloy in presence of Sodium salts at 850°C - Mohammed Misbahul, Amin (Academy Science Publishers/African Academy of Sciences (AAS), 2009)
The hot corrosion behaviour of Nickel-200 industrial alloy has been investigated in presence of Na2S04, NaCI, NaN03, Na2C03 and Na202 at 850°C in flowing air. The hot corrosion kinetic and effect of salt deposition on the corrosion rate were studied. The scale morphologies were determined on the basis of X-ray diffraction and Scanning electron microscopic techniques. It has been shown that an alloy corrodes at different rate in presence of different sodium salts although each salt contains the same amount of sodium equivalent to Na20.